1998
DOI: 10.1111/j.1439-0507.1998.tb00382.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of tinea barbae successfully treated with terbinafine

Abstract: Terbinafine was remarkably effective in tinea barbae due to Trichophyton rubrum on the cheek in front of the right ear in a 75-year-old man. This patient also showed tinea pedis and unguium, but these were due to Trichophyton mentagrophytes and were unrelated to the tinea in the cheek. This patient showed an atypical clinical picture slightly different from that during the initial visit, requiring histological differentiation from trichophytic granuloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…15 Regarding etiologies among the dermatophytoses, T. rubrum has been shown to have a high incidence as a causative agent. 16,18,20 In our study, the most frequently isolated dermatophyte from different body regions was T. rubrum.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…15 Regarding etiologies among the dermatophytoses, T. rubrum has been shown to have a high incidence as a causative agent. 16,18,20 In our study, the most frequently isolated dermatophyte from different body regions was T. rubrum.…”
Section: Discussionmentioning
confidence: 58%
“…Studies have shown that bifonazole plus urea can be useful in this situation. [12][13][14]16 The application of urea along with butenafine can also result in earlier improvement of dermatological symptoms of hyperkeratotic-type tinea pedis 15 as well as when associated with lanoconazole.…”
Section: Introductionmentioning
confidence: 99%
“…Griseofulvin is rarely used today, given its multiple adverse reactions. Oral terbinafine, 125 mg per day for 12 weeks, has been reported to be effective [24]. Adverse effects include nausea, abdominal pain, diarrhea, rash, liver enzyme abnormalities, and visual disturbances.…”
Section: Treatmentmentioning
confidence: 98%
“…In theory, the course of therapy would be longer for tinea barbae than for a superficial dermatophytosis but shorter than for onchomycosis. Courses ranging from 6 to 12 weeks have been reported to be effective [5,24].…”
Section: Treatmentmentioning
confidence: 98%
See 1 more Smart Citation